Direct-to-Consumer Testing: The Business With Lifestyle Tests. Issue 3 (September 2017) - Orth, Matthias
Abstract : Abstract: Medical treatment by a physician consists of diagnosing the disease of a patient and choosing the right treatment for the disease. In most cases, medical diagnosing uses laboratory testing, and in most countries, laboratory testing is regarded as an integral part of health care. Certain country-specific regulations even restrict the access only to physicians such as for the test kits or prohibit to addressing the patient directly with the laboratory report. The idea behind these regulations originates from patient safety issues with the special situation in health care with, for example, the asymmetric situation between highly trained health care professionals and the medically illiterate patient who needs a particular protection such as by sophisticated legal restrictions. Direct-to-consumer testing (DTCT) challenges these restrictions. The idea behind DTCT is the direct access of the "consumer" (the former "patient") to medical test results and the concept to self-empower the "consumer" (with the concept of "4P-medicine"). In many cases, Internet technologies are used both to offer convenience to the "consumer" and to circumvent national legal restrictions in health care. Without doubt, some DTCT such as glucose self-testing are medically necessary and beneficial for the patients. However, in many other cases, DTCTs are even a severe threat to patients' safety and aimed to maximize the profits of the vendors only. A particular challenge is the nearly unlimited number of tests available and the blurred nonmedical interpretation of the DCTC laboratory tests performed.